2020
DOI: 10.1111/jce.14342
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of cardiac synchrony in left bundle branch pacing: Insights from echocardiographic research

Abstract: Aim: The aim of this study is to assess if left bundle branch pacing (LBBP) can preserve physiological cardiac synchrony and deliver favorable hemodynamic effects.Methods: Consecutive patients undergoing dual chamber pacemaker implantation for sick sinus syndrome (SSS) and a normal cardiac function with a narrow QRS complex were recruited for the study. Electrocardiogram and echocardiographic examinations were performed during ventricular pacing-on and native-conduction modes. The QRS duration (QRSd), systolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
81
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 30 publications
10
81
0
2
Order By: Relevance
“…Some studies also confirmed the short‐term and medium‐term feasibility and stability of LBBP 27‐29 . It has been proved that reduction in electric dyssynchrony was reflected by the shorter QRS duration and stim‐LVAT during LBBP, which could translate to acute hemodynamic effects compared with RVP 7,27 . In our present study, majority of patients with PVs succeeded in LBBP and presented a narrow pQRSD and short stim‐LVAT.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Some studies also confirmed the short‐term and medium‐term feasibility and stability of LBBP 27‐29 . It has been proved that reduction in electric dyssynchrony was reflected by the shorter QRS duration and stim‐LVAT during LBBP, which could translate to acute hemodynamic effects compared with RVP 7,27 . In our present study, majority of patients with PVs succeeded in LBBP and presented a narrow pQRSD and short stim‐LVAT.…”
Section: Discussionsupporting
confidence: 83%
“…Zhang et al confirmed the effectiveness of LBBP in heart failure patients complicated with LBBB 26 . In our previous study, we convinced that LBBP may bring about better electrical and mechanical synchrony compared with RVP 7 . Some studies also confirmed the short‐term and medium‐term feasibility and stability of LBBP 27‐29 .…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, LBBP is a relatively novel physiological pacing strategy, and the effects of LBBP on cardiac synchrony remain vague 23,24 . LBBP could either directly capture LBB, LBB together with nearby myocardium, or nearby myocardium, and then propagates to LBB, eventually activating the whole left ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…When the article 1 was first published online, the data of baseline QRSd in Table 1 was not updated.…”
Section: Parameters Lbbp (N = 40) Rvsp (N = 38) P‐valuementioning
confidence: 99%